Serie periodística online en diversos formatos sobre el mercado artesanal pesquero de chorrillos: “Mar afuera” - Leo Melgar, Stephanie Nicole (2020)
The fishing cove of Chorrillos is part of the history, tradition and identity of the district. Since its creation it has been visited by a thousand Peruvians and tourists; however, it has been neglected over the years. In order to revitalize the space, give it a new meaning and be appreciated with a modern look, a journalistic series was produced that captures and exposes the essence of the place. For this reason, this work consists of a chronicle, three photo galleries, a video report and several testimonies of chorrillanos, whose content revolves around the fishermen's wharf.